Analysis Of Factors Affecting The Demand For Salted Fish On The Malabero Coast Of Bengkulu City - Raditya , Zhazha Aura; Fariadi , Herri; Nurmalia , Ana Nurmalia (Multidisciplinary Journals, 2024)
This research is motivated by the increasing demand for salted fish in Bengkulu City, to find out the factors that affect the demand for salted fish, this research was conducted. One of the areas famous for salted fish is the coastal area of Malabero Beach, Bengkulu City. The objectives in this study include (1) To determine the level of demand for salted fish on the coast of Malabero Beach, Bengkulu City. (2) To analyze what factors affect the demand for salted fish on the coast of Malabero Beach, Bengkulu City. This research was conducted at the stalls of salted fish sellers within the scope of Malabero Village. With a sample of 96 people who are salted fish consumers. Factors that are thought to affect salted fish demand consist of salted fish prices, chicken egg prices, number of family members, total family income, and consumer tastes. The data analysis used is with a Likert scale, and multiple linear analysis. The conclusions of this study are (1) the level of demand for salted fish on average 280.2 which is included in the moderate category. (2) factors that have a real effect on the demand for salted fish are family income, and consumer tastes.